Case report of a neonate with ocular toxoplasmosis due to congenital infection: estimation of the percentage of ocular toxoplasmosis in Greece caused by congenital or acquired infection - Asproudis I (Dove Medical Press, 2013)
Ioannis Asproudis,1 Ioannis Koumpoulis,1 Chris Kalogeropoulos,1 Georgios Sotiropoulos,1 Margarita Papassava,2 Miltiadis Aspiotis11Department of Ophthalmology, Medical School, University of Ioannina, 2Neonatal Intensive Care Unit, University Hospital of Ioannina, Ioannina, GreeceAbstract: We report a case of a newborn male child with congenital toxoplasmosis. During pregnancy seroconversion occurred and positive titers of antitoxoplasmic antibodies (immunoglobulin M and G) were found in the mother, in the third trimester. She received treatment with spiramycin. After birth, the neonate presented with chorioretinitis and intracranial calcifications. The neonate received treatment with pyrimethamine, sulfadiazine, and leucovorin for 1 year. In addition to using a previously described method, we report for the first time in Greece an estimation regarding the percentage of ocular toxoplasmosis caused by congenital or acquired infection. We estimate that ocular toxoplasmosis in Greece is caused in 7% of the cases by congenital infection, and in 93% of the cases by acquired infection.Keywords: toxoplasmosis, ocular, congenital, acquired, chorioretinitis